Interleukin‐13 Inhibits Expression of cyp27b1 in Peripheral CD14+ Cells That Is Correlated With Vertebral Bone Mineral Density of Patients With Ulcerative Colitis. Issue 2 (7th September 2016) - Ding, Qingfeng; Zhou, Hao; Yun, Bo; Zhou, Lingjie; Zhang, Ning; Yin, Guoyong; Fan, Jin
ABSTRACT: Osteoporosis is a common problem in aged people and those with related diseases, such as inflammatory bowel diseases. Deregulation of vitamin D metabolism plays a role in the pathogenesis of osteoporosis. Micro RNA (miR) can regulate cytokine expression in cells. This study test a hypothesis that inflammatory cytokine interleukin (IL)‐13 increases miR‐19a to compromise cyp27b1 (a vitamin D hydroxylase) in peripheral CD14 + cells. Bone mineral density of L2–L4 was measured in 20 patients with ulcerative colitis (UC) and 20 healthy subjects. Peripheral CD14 + cells were isolated from healthy people and patients with UC. Expression of cyp27b1 by CD14 + cells was analyzed in the presence or absence of IL‐13 in the culture. We observed that bone mineral density (BMD) in UC patients was significantly lower than healthy subjects. The BMD is negatively correlated with miR‐19a in peripheral CD14 + cells. MiR‐19a in peripheral CD14 + cell was correlated with serum IL‐13 in UC patients. Expression of cyp27b1 in peripheral CD14 + cells was correlated with miR‐19a and serum IL‐13 in UC patients. IL‐13 suppressed cyp27b1 expression in CD14 + cells. IL‐13 increased expression of miR‐19a in CD14 + cells. IL‐13 suppresses cyp27b1 expression in peripheral CD14 + cells via up regulating miR‐19a expression. J. Cell. Biochem. 118: 376–381, 2017. © 2016 Wiley Periodicals, Inc. Abstract : In a group of patients with inflammatory bowel disease, the bone mineral density is negatively correlated with the levels of micro RNA (miR)‐19a in CD14 cells of the peripheral blood system. miR‐19a mediates the effect of interleukin‐13 on suppressing the expression of cyp27b1 in CD14 cells.